Kalimat Larangan: Kajian Struktur dan Fungsinya dalam Penafsiran Al-Qur’an - Husnul Khatimah; Andi Miswar; Mohamad Harjum (Yayasan Azhar Amanaa Yogyakarta, 2026)
The prohibitive expression (al-nahy) is one of the forms of inshā’ ṭalabī (directive speech) that plays a significant role in understanding the meanings of the Qur'an and the formulation of Islamic legal rulings (aḥkām shar‘iyyah). This study aims to analyze the grammatical structure and functions of prohibitive expressions in Qur'anic interpretation through a library research approach using a descriptive-analytical method. The findings reveal that prohibitive expressions appear in several forms, namely the imperfect verb (fi‘l muḍāri‘) preceded by lā al-nahy (the prohibitive lā), the direct use of prohibitive expressions, and the use of the word ḥarrama (